Effect of sowing direction and crop geometry on water use efficiency and productivity of Indian mustard (Brassica juncea. L.) in semi arid region of India (Journal of Oilseed Brassica, 2026)
Indian mustard [Brassica juncea (L.) Czern & Coss.] is an important oilseed crop for the rainfed, semi-arid region of north-western plains of India. The best direction of sowing with respect to yield is still not clear. Therefore, two Indian mustard varieties differing in their phenotypes (erect and spreading type) were grown in two sowing directions [North-South (NS) and East-West (EW)] along with broadcast to study the effect of direction of sowing, and planting geometry on the actual evapotranspiration (AET), water use efficiency (WUE), biomass production, and yield. Accumulated AET was studied to be higher in the EW direction than in NS sown plots. Direction wise NS sown plots showed higher WUE, and better AET-yield production function (higher coefficient of determination) than the EW sown plots. EW sown plots produced the highest seed yield followed by broadcast sown, and NS sown plots, and proved to be the best in terms of WUE, biomass production and seed yield.